Comparative Effect of use of Graphic Organizers on Students’ Learning Outcomes in Organic Chemistry - Bashirat Titilope Imam; Adekunle Solomon Olorundare (Unnes Science Education Journal, 2023)
The purpose of this study is to determine the comparative effectiveness of the use of concept map and mind map graphic organizers on students’ learning outcomes in organic chemistry. This research adopted a quasi-experimental design involving a 3X2 pre-test post-test non-randomized and non-equivalent control group design. The study is premised on the dual coding theory of cognition, and involved 183 respondents whom were purposively selected from three intact classes. Data for the study was gathered through an organic chemistry achievement test whose reliability was determined through a test retest method and a reliability index of 0.74 was obtained. Data was analyzed using t-test and Analysis of Covariance. Findings show that there was a significant difference between the achievement of students taught organic chemistry using concept map graphic organizers and those taught with the mind map graphic organizer (F(1,118)= 7.04, p<.05). Using t-test statistics, findings also indicated that there was no significant difference in the achievement of male and female students when exposed to either concept map (t(75)= .47, p = .63) or mind map graphic organizer (t(42)= .64, p = .52). Hence, it was concluded that mind map is a more effective tool for learning organic chemistry when compared to the concept map. Irrespective of students’ gender, either of concept map or a mind map can help improve students’ achievement in organic chemistry.